Knowledge Level and Personal Hygiene Related To The Incidence of Scabies at Darul Hikmah Islamic Boarding School In Medan City, 2023 - Nasution, Ika Yusnasari; Murlina, Nelli (Buletin Farmatera, 2026)
Abstract: Scabies is an infectious skin disease caused by infestation and sensitization to Sarcoptes scabiei var. hominis and its products. Supporting factors for the occurrence of scabies were poor sanitation, which could attack humans who lived in groups; poor personal hygiene; poor sanitation; low socioeconomic status; and poor behavior that supports health and plays a role in skin diseases. This type of research was an observational analysis with a cross-sectional approach on 253 students at the Darul Hikmah Islamic Boarding School in Medan using the total sampling method. The sample would be given a questionnaire, then the data would be collected and processed using the chi-square test. Univariate analysis obtained the distribution of knowledge levels, mostly good, with as many as 149 people (58.9%) with sufficient personal hygiene, as many as 167 people (66%), and most students do not have scabies, as many as 161 people (63.6%). The results of the analysis using the Chi-Square test showed a relationship between the level of knowledge and personal hygiene on the incidence of scabies, with a value of p = 0.001 (p 0.05). There was a relationship between the level of knowledge and personal hygiene of the students and the incidence of scabies in Pesantren Darul Hikmah, Medan City.